Influencing factors of college students’ sports participation - Tang Yao; Hasnol Noordin; Pathmanathan K. Suppiah; Soon Singh Bikar Singh (Human Resource Management Academic Research Society (HRMARS), 2024)
Regular participation in exercise can prevent diseases and maintain health. However, adolescents around the world are not physically active enough. This study aims to sort out the factors influencing college students' participation in sports, to promote college students to participate in more sports, and maintain physical and mental health. After sorting out the factors that affect college students' sports participation, it was found that personal attributes, sports facilities, role models, peers, social culture, smartphones, health management, and academic performance may all be factors that affect college students' sports participation. School administrators can start from these factors to create an environment more conducive to college students' sports participation, eliminate the adverse effects of these factors, and allow these factors to play a positive role in encouraging more college students to participate in sports.